PENGARUH PEMANGKASAN DAUN BAGIAN BAWAH TERHADAP PRODUKSI JAGUNG MANIS (Zea mays var. saccharata Sturt) - Augus Y. M. Sumajow; Johannes E. X. Rogi; Selvie . Tumbelaka (AGRI-SOSIOEKONOMI, 2016)
The purpose of this study was to determine the effect of trimming the bottom leaves to the increased production of sweet corn crop. This research was arranged in a completely randomized design (CRD) with 4 treatments and repeated 5 times. Pruning is done at the age of 50 days after planting. The results obtained from this study are pruning significant effect on the rising corncob where the highest rates in the third pruning leaves the bottom (P3) weighing 333.04 g. In the variable length cob, cut 3 pieces (P3) gives the most high, 21.25 cm while trimming treatment 1 piece (P1) and a second piece (P2) shows the results are not significantly different from each other but significantly different from that of the untreated (P0) , While on the cob entire circumference of the variable level of treatment (P1, P2, P3) results are not significantly different from each other but all three significantly different from that of the untreated (P0) ddengan highest yield is in P3 which is 17.27 cm. from these results it can be concluded that treatment of the bottom leaf pruning can increase the production of sweet corn.